Naturally occurring physalins from the genus Physalis: A review. (November 2021) - Wu, Jiangping; Zhao, Jianping; Zhang, Tao; Gu, Yucheng; Khan, Ikhlas A.; Zou, Zhongmei; Xu, Qiongming
Abstract: Physalins, including physalins and neophysalins, are a class of highly oxygenated ergostane-type steroids. They are commonly known by the name of 16, 24- cyclo -13, 14- seco steroids, in which the disconnection of C-13 and C-14 produces an eight or nine-membered ring and the carbocyclization of C-16 and C-24 generates a new six-membered ring. Meanwhile, the oxidation of C-18 methyl to carboxyl group forms a 18, 20-lactone, and the oxidation of C-14 and C-17 gets a heterocyclic oxygen acrossing rings C and D. Additionly, physalins frequently form an oxygen bridge to connect C-14 to C-27. Physalins are a kind of characteristic constituents from the species of the genus Physalis (Solanaceae), which are reported with a wide array of pharmacological activities, including anticancer, anti-inflammatory, immunoregulatory, antimicrobial, trypanocidal and leishmanicidal, antinociceptive, antidiabetic and some other activities. Herein, the research progress of physalins from the genus Physalis during the decade from 1970 to 2021 on phytochemistry, pharmacology, pharmacokinetics and application in China are systematically presented and discussed for the first time. Graphical abstract: Image 1 Highlights: Physalins act as the primary chemical constituents of the genus  Physalis. A total of 78 physalins with extensive pharmacological activities have been isolated from genus Physalis until now. The research progress of physalins from the genus Physalis during the decade from 1970 to 2021 are summarized.